Optical and mechanical properties of lyotropic liquid crystal using triton X-100, aerosil 200, and tapioca starch - Muhasshim, Arishah; Mohammad Isa, Mohd Ikmar; Sabri, Norhazmin; Saifful Kamaluddin, Muzakir (2011)
This work focus on the study of the optical and mechanical properties of Tapioca Starch/ H2O/ Triton X-100/ Aerosil®200 lyotropic liquid crystal(LLC). Polarize Optical Microscopy, Rheology and Small-and-Wide Angle X-ray Scattering method was used to determined the properties of the LLC. Fifty three samples with different composition ratio were prepared and characterized. The viscosities of the samples were studies at different temperature of 15, 25 and 45˚C in order to study the effect of temperature on the samples. Ternary diagram obtain from this work show that four phases occur in the composites or samples, namely Lamellar, Hexagonal, Micellar and Discotic. The spacing lattice (d), of the composites was in the range of 76.72Ǻ to 122.26Ǻ. The study shows that at low temperature, the liquid acts as a lubricant and the lyotropic flows easily while at higher temperature, the liquid is unable to fill the gaps created between particles, and friction greatly increases, causing an increase in viscosity. The Tapioca Starch/ Triton X-100/ water/ Aerosil®200 LLC prepared in this work produce similar properties of shear thickening fluid.